The substitution of Carrera Magisterial: a public policy learning process? - Jemyna Rueda Hernández; Pedro Flores-Crespo (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2017)
This article analyses the substitution process of the Carrera Magisterial (CM) Program by the new Programa de Promoción en la Función por Incentivos en Educación Básica (PPFIEB) in Mexico. These programs are based on an incentive scheme for elementary teachers in recognition to their work since 1992. Due to the absence of theoretical references in the field of the public policy in education, it is the aim of this article to find out if the adequacies to this economic incentive scheme respond to a policy-oriented learning process (SABATIER; EIBLE, 2007). A retrospective analysis of the teachers‟ professional policies has been conducted, specifically of the CM program and its changes from its creation in 1992 until its substitution in 2015. Based on our analysis it is concluded that it seems to exist a policy-oriented learning process in the substitution of the CM by the PPFIEB. However, there two relevant points to highlight here: first, CM has changed more for political reasons than for scientifically proven evidence. Second, the new Program (PPFIEB) seems to take into account part of this evidence but without a complete incorporation of it.